The Effectiveness of Online Learning Usage for English Subject in Covid-19 Pandemic - Santy Christinawati; Wahyu Trimastuti (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
The effectiveness of Polytechnic Piksi Ganesha e-learning as one of the official learning media for teaching and learning. This study aims to describe the effectiveness of online learning using Piksi Ganesha ELearning in the Health Faculty during the COVID-19 pandemic. This research is descriptive quantitative research with a survey design. The sample of this study was all students of the Medical Record Study Program, amounting to 100 students. The data collection instrument uses a questionnaire packaged into google form. Data analysis used descriptive statistics. The results showed that online learning using Piksi Ganesha’s ELearning in the covid-19 pandemic in the Medical Record study program was quite effective. This is revealed from online learning using Piksi Ganesha E-Learning, The questionnaire used consists of four indicators, namely (1) student concentration in online learning with Piksi Ganesha ELearning is 725, (2) student understanding of learning materials is 88%, (3) student motivation in online learning is 88%, (4) student learning outcomes in online learning is 97%. The results of the study show that online learning using Piksi Ganesha E-Learning in the covid-19 pandemic in the Medical Record study program is quite effective. The results of this study have implications for the sustainability of the use of Piksi Ganesha’s E-learning as a learning platform used by Piksi Ganesha lecturers and students.